Tata Kelola Sumber Daya Manusia Dalam Adversity Quotient Di KOPMA UIN Sunan Kalijaga Yogyakarta - Nur Khamid Al Mi’roj; H. Khamim Zarkasi Putro (Thawalib: Jurnal Kependidikan Islam, 2022)
Human resource management in adversity quotient in student cooperatives is an institution that focuses on cooperative education and training and human resource development. The training and development of potential members is the domain of the Human Resource Development division which is carried out by the daily manager. This section conducts a survey to members by distributing a questionnaire of member needs which are then realized. The level is three management/two and a half years. This career is divided into two types, namely management career path and membership career path. The compensation system is divided into two types, namely financial and non-financial compensation. The concept and development of Human Resources in Islamic religious education training, namely Allah commands humans to seek knowledge, seek knowledge with the intention of worship, calls for good teaching, the existence of methods and development of human resources in Islam, the importance of paying attention to morality and physical appearance, and Islam that encourage people to earnestly improve performance.